EU FADN farm classification: first experience of Ukraine in a European perspective - Yashchenko, L. O.; Marongiu, S.; Prokopenko, O. M.; Kruglyak, H. I. (Statistics of Ukraine, 2025)
The article analyzes the typology of agricultural holdings within the Farm Accountancy Data Network (FADN) and its impact on the formation of the common agricultural policy. The study emphasizes the importance of FADN as a tool for collecting, processing and analyzing economic data on farms, which contributes to the development of effective management strategies and policy-making processes.Particular attention is paid to methodological issues of farm classification and potential benefits of adapting EU experience to the Ukrainian specifics of the agricultural sector. The article describes the methodology used for typological classification based on economic size and farm type (such as specialist crop or livestock farms). It involves grouping farms based on Standard Output (SO). This classification helps identify structural characteristics, income levels, and production focus among farms. The procedure of the farm classification can be described in the following steps: Stage 1: Calculation of Standard Output Coefficients (SOC). Stage 2: Calculation of SO for each production (crops and livestock). Stage 3: Calculation of the total SO of the farm. Stage 4: Determination of the Economic Size of the farm. Stage 5: Determination of the Type of Farm. In addition, the study identifies problems associated with data collection, methodological discrepancies and the integration of small farms into the FADN system.The authors emphasize that the importance of maintaining harmonized typological classifications across EU member states. Such consistency ensures the reliability of cross-country comparisons and supports the formulation of effective agricultural policies that address the diversity of farming structures within the Union. So, the implementation of FADN in Ukraine will contribute to the harmonization of agricultural statistics and comparative analysis at the European level. The article concludes that further improvement of the typology framework and strengthening of digitalization efforts will contribute to better policy formulation and sustainable development of agriculture of Ukraine.